SiRNA-Cyp4a14 and diabetic nephropathy: silencing of Cyp4a14 by siRNA inhibits proliferation and fibrosis of mesangial cells - Wang, Suyu (Int J Clin Exp Pathol, 2017)
Diabetic nephropathy (DN) is one of the most common complications of diabetes, which increases mortality of diabetic patients. In recent years, many studies have confirmed that patients with diabetes are often accompanied by lipid metabolism disorders. Peroxisome proliferator-activated receptor (PPARs) is known to play pivotal roles in the regulation of insulin signaling, glucose and lipid metabolism. Cyp4a14 was confirmed to be the PPARα-target marker genes. We attempt to explore the biological role of Cyp4a14 in diabetic nephropathy. In our previous study, lncRNA microarray analysis showed us Cyp4a29-ps, Cyp4a14, Cyp4a12a and Cyp4a12b were the nearby mRNAs of lncRNA CYP4B1-PS1-001, we chose Cyp4a14 as our candidate. Renal cortical tissues were collected from db/db and db/m mice, and the mRNA expression of Cyp4a14 in diabetic tissue was significantly higher than that in normal tissue. And the expression of Cyp4a14 in mesangial cells cultured in high glucose was higher than that in low glucose by qualitative reverse transcription polymerase chain reaction (qRT-PCR) and Western blot analysis. By Cell Counting Kit-8 (CCK8) and colony- forming ability, it is found that siRNA-Cyp4a14 treatment effectively suppressed the proliferation of mesangial cells. From our results, the protein expression of proliferating cell nuclear antigen (PCNA), Cyclin D1, Collagen I, and Fibronectin were all regulated dramatically in siRNA-Cyp4a14 group compared with the negative control group. Our data indicated that siRNA-Cyp4a14 inhibits proliferation and fibrosis of mesangial cells, which can be considered as a therapeutic target for diabetic nephropathy.